Prevalence of intestinal parasitic infections among patients attending al ’ahwar sector in Nasiriyah City southern Iraq - J. Alrikaby, Nuha (University of Thi-Qar Journal, 2022)
Gastrointestinal helminthes and protozoan parasites can cause ,acute and chronic human infections , There is inadequate reliable studys on the epidemiology of these parasites among patients attending al ’ahwar sector in Thi- Qar province . This study was conducted using health centers data obtained from al’ ahwar Laboratories Unit. A total of 801 stool samples were recorded from January 2017-December 2017. Intestinal parasitic infections were recovered in 40.7% (326) of the stool samples . The commonest pathogenic parasite was Entamoeba histolytica . the prevalence of this protozoon 25.2%, then the nematode Enterobius vermicularis, the prevalence of this helminthes was 10.9%. finally the protozoon Giardia lamblia the prevalence was 4.6%.